Is it easy to go green? Consumer perception and green concept - Rezai, Golnaz; Phuah, Kit Teng; Mohamed, Zainal Abidin; Shamsudin, Mad Nasir (Science Publications, 2013)
A series of health consciousness, environmental and animal welfare issues have brought about awareness among consumers to become conscious of their consumption behaviour. Consumers have begun to search for green products were produced under environmentally friendly conditions and considered green by nature. However, this is only the beginning of the development of the green concept in Malaysia. Thus the objective of this study is to determine the relationship between the socio demographic variables towards the consumers' perception towards the green concept. Structured questionnaire was design as an instrument to gather information on green consumer perception and 1360 submitted their responses to the questionnaire. Descriptive analysis, Chi-square and binary logistic model were used to accomplish the objectives of this study. The result shows that selected socio-demographic variables such as education level, income, age and marital status significantly influence the consumers' perception towards the green concept. The results also indicate that consumers' opinion about going green is the best way to save the environment and make green products and green practices available in Malaysia. Consumers should be aware of and understand the importance of green products and how the information related to the green concept can affect their future purchases. Therefore, government or other institutions can carry out an effective product awareness program in exhibitions, trade shows, campaigns and seminars to introduce the green concept to the markets. Food producers, processors and manufacturers should have enough knowledge and information about how to produce or process green products by following Malaysian rules and regulations as well as the international norms.